Konstruksi Masyarakat Urban dalam Kumpulan Puisi Wong Kam Pung Karya F. Aziz Manna (Sebuah Catatan Simpatik di Era Merdeka Belajar) - M. A. Haris Firismanda; Lina Puryanti (IKIP PGRI Bojonegoro, 2023)
Abstract: In this era of independent learning there are many learning resources that can be used as a vehicle for knowledge, including literary works, especially literary works in the form of poetry. Literary work is a mimesis of the real world, so its existence can inspire students to live life. This study discusses the construction of urban society in a collection of poems entitled